1989
DOI: 10.1126/science.2564702
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Behaviors in Infant Rhesus Monkeys: Environmental Cues and Neurochemical Regulation

Abstract: To survive, primates must detect danger in time to activate appropriate defensive behaviors. In this study, the defensive behaviors of infant rhesus monkeys exposed to humans were characterized. It was observed that the direction of the human's gaze is a potent cue for the infant. Infants separated from their mothers were active and emitted frequent distress vocalizations. When a human entered the room but did not look at the infant, it became silent and froze in one position. If the human stared at the infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
324
2
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 295 publications
(346 citation statements)
references
References 24 publications
18
324
2
2
Order By: Relevance
“…Results demonstrated that significant contributions from the right dlPFC [F-change (1,19) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Results demonstrated that significant contributions from the right dlPFC [F-change (1,19) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 97%
“…Importantly, the time course of FDG uptake coincides with that of the separation response. The behaviors occurring during social separation were videotaped and assessed by trained raters (1). After the 30-min separation period, the animals were anesthetized with ketamine (15 mg͞kg) delivered intramuscularly, placed on isofluorothane gas anesthesia (1-2%), and scanned in the microPET P4 scanner (Concorde Microsystems, Knoxville, TN) (11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations